X-ray-initiated photodissociation of the glycine molecule - Li Fang; Hui Xiong; Edwin Kukk; Vladmire S. Petrovic; Nora Berrah (AMER PHYSICAL SOC, 2022)
We investigated the charge distribution and dissociation dynamics of glycine (NH2CH2COOH) molecules irradiated with 310-eV x rays from the Advanced Light Source synchrotron. With simultaneous measurements of the fragment ion yield, dissociation angle, and kinetic energy, we were able to reconstruct a three-dimensional image of the x-ray-initiated molecular dissociation. Using coincidence and correlated analysis and applying a systematic comparison of properties of ion species, we partially disentangled the fragmentation pathways and identified the most probable fragmentation channels that lead to the observed fragment ions. In addition, we showed anisotropic angular distributions of dissociation subsequent to core-level photoionization and Auger decay and found an association between the initial bond-breaking sites and the kinetic energies of the final fragment ions.